Analisa Perbedaan Pendapatan Mikro Sebelum dan Selama Menerima Pinjaman Kredit dari PNM Madani Probolinggo - Noor Farid (Journal on Education, 2021)
This study aims to determine the difference between micro income before and during receiving credit loans from PNM Madani to Micro, Small, Medium Enterprises and Cooperative (UMKMK) actors in Probolinggo. The research used a quantitative descriptive research method which was carried out through data collection with primary and secondary data, a population of 53 and the sample in this study were 10 UMKMK actors who were registered for 3 years and still resided in Gending and made credit loans at PNM Madani for the period of 2020. The data analysis technique in this study was a different test of the average of two paired samples (t-test). The results showed that the difference in Micro Income before and during receiving Credit Loans from PNM Madani to UMKMK actors was seen from the data analysis with the t-test, the t-count value was 8,168 beyond the limit value of t table (8,168> 2,045) so it can be stated that there is a difference Recipients before and after receiving Credit Loans from PNM Madani to UMKMK actors in Probolinggo.